A systems-based approach to uterine fibroids identifies differential splicing associated with abnormal uterine bleeding - Chen-Yi Wang; Martin Philpott; Darragh P O’Brien; Anne Ndungu; Jessica Malzahn; Marina Maritati; Neelam Mehta; Vicki Gamble; Beatriz Martinez-Burgo; Sarah Bonham; Roman Fischer; Kurtis Garbutt; et al. (Communications Medicine)
Abstract Background Uterine fibroids (UFs), benign tumours prevalent in up to 80% of women of reproductive age, are associated with significant morbidity, including abnormal uterine bleeding, pain and infertility. Despite identification of key genomic alterations in MED12 and HMGA2, the pathogenic mechanisms underlying UFs and heavy menstrual bleeding (HMB) remain poorly understood. Methods To correlate systematically genetic, transcriptional and proteomic phenotypes, we conducted an integrative multi-omic approach utilising targeted DNA sequencing, RNA sequencing and proteomic methodologies, encompassing fibroid, myometrium, and endometrium tissues from 91 patients. Results In addition to confirming the presence of MED12 mutations, we identify variants in AHR and COL4A6. Multi-omic analysis of endometrium identifies latent factors that correlate with HMB and fibroid presence with driver mutations of MED12, AHR, and COL4A6, which are associated with pathways involved in angiogenesis, extracellular matrix organisation and RNA splicing. We propose a model, supported by in vivo evidence, where altered signalling of MED12-mutated fibroids influences RNA transcript isoform expression in endometrium, potentially leading to abnormal uterine bleeding. Conclusions This study presents a comprehensive integrative approach, revealing that genetic alterations in UF may influence endometrial function via signalling impacts on the RNA splicing mechanism. Our findings advance the understanding of complex molecular pathways in UF pathogenesis and UF-associated endometrial dysfunction, offering insights for targeted therapeutic development.